1982
DOI: 10.1136/oem.39.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in the British rubber industry.

Abstract: Although it is over 30 years since an excess of bladder cancer was first identified in British rubber workers, the fear has persisted that this hazard could still be affecting men working in the industry today. Furthermore, suspicions have also arisen that other and hitherto unsuspected excesses of cancer might be occurring. For these reasons 33 815 men, who first started work in the industry between 1 January 1946 and 31 December 1960, have been followed up to 31 December 1975 to ascertain the number of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Excesses in esophageal cancer among brewery workers [Adelhardt et al, 1985;Olsen and Jensen, 19871, waiters [Petersen and Milham, 1980;Andersen et al, 1989;Bulbulyan et al, 19921, and perhaps sales agents and butchers [Milham, 19831, may be related in part to alcohol drinking and smoking. However, the reduction in risk among professional and agricultural workers demonstrated in this study and in a number of previous investigations [Saftlas et al, 1987;Kato et al, 1990;Blair and Zahm, 19911 may in part be due to their relatively healthy lifestyle, including low exposure to smoking and alcohol [Pomrehn et al, 1982;Ronco et al, 19921. Our finding of an excess incidence of esophageal cancer among men employed in rubber industry, particularly in vulcanizing shops, is consistent with those of several earlier investigations [Parkes et al, 1982;Norell et al, 1983;Sorahan et al, 19891, but not others [Fox and Collier, 1976;Neugut and Wylie, 19871. A nearly significant twofold risk of esophageal cancer was associated with employment in the gas, electricity, and water plants in an earlier case-control study [Magnani et al, 19871, but risks for specific industries within this category was not reported. In the current study, increased incidence was largely confined to employment in gas plants and public cleaning works.…”
Section: Discussionsupporting
confidence: 94%
“…Excesses in esophageal cancer among brewery workers [Adelhardt et al, 1985;Olsen and Jensen, 19871, waiters [Petersen and Milham, 1980;Andersen et al, 1989;Bulbulyan et al, 19921, and perhaps sales agents and butchers [Milham, 19831, may be related in part to alcohol drinking and smoking. However, the reduction in risk among professional and agricultural workers demonstrated in this study and in a number of previous investigations [Saftlas et al, 1987;Kato et al, 1990;Blair and Zahm, 19911 may in part be due to their relatively healthy lifestyle, including low exposure to smoking and alcohol [Pomrehn et al, 1982;Ronco et al, 19921. Our finding of an excess incidence of esophageal cancer among men employed in rubber industry, particularly in vulcanizing shops, is consistent with those of several earlier investigations [Parkes et al, 1982;Norell et al, 1983;Sorahan et al, 19891, but not others [Fox and Collier, 1976;Neugut and Wylie, 19871. A nearly significant twofold risk of esophageal cancer was associated with employment in the gas, electricity, and water plants in an earlier case-control study [Magnani et al, 19871, but risks for specific industries within this category was not reported. In the current study, increased incidence was largely confined to employment in gas plants and public cleaning works.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, the observed differences in DNA adduct levels by production functions were comparable to the distribution of the urinary bladder cancer risk in the past. Urinary bladder cancer risk was then observed in various work areas but mostly in the compounding and mixing departments [Parkes et al, 1982;Sorahan et al, 1986], which suggests that the observed DNA adducts in this study might be related to exposure to one or more constituents of raw rubber chemicals, carbon black, or process oils used within the rubber industry. Only structural characterization of the detected DNA adducts, however, could have given more insight into the chemical origin of these DNA adducts.…”
Section: Discussionmentioning
confidence: 77%
“…Finally, any ''healthy worker effect'' was avoided, since workers were internally compared. 23 There have been reports on positive associations between various occupational groups and risk of gastric cancer, 10,12 notably ''dusty'' occupations, e.g., coal and tin mining, [24][25][26][27][28][29] metal processing, [30][31][32][33][34][35] rubber manufacturing [36][37][38][39][40] and carpentry or construction work. 10,12 Other dusty work environments have also been implicated in the etiology.…”
Section: Discussionmentioning
confidence: 99%